PERVALENCE OF INTESTINAL HELMINTHIASIS AMONG SETTLED NOMADS AND THOSE WITH MOVING HABITS - NO AUTHOR (Tehran University of Medical Sciences, 1974)
The Prevalence of various Intestinal helminthiases among the inhabitants of 7 villages was compared with that among the nomadic Bakhtiari tribe with its migratory habits. Stool examination of 736 nomads and 784 persons of the same ethnic group settled in 7 villages showed that, among the settled population, the prevalence of infection with Ascaris, Trichostrongylus spp., Trichuris trichiura, Hymenolepis nana, Taenia saginala and Enterobius vermicularis was 42.31%, 14%, 3.9%, 5.4%., 1%, and 6%, respectively. The prevalence of infection with the above-mentioned helminthes among the tribe with migratory habits was respectively 9.2%, 86.9%, 0.5%, 4.7%, 0.5%, 1%. The species of Trichostrongylus found among the inhabitants of the villages were in order of frequency, orientalis, colubriformis, axei, vitrinus and capricola, while the species expelled by nomadic patients after treatment were, in order of frequency, T. colubriformis, T. orientalis, T. axei, T. capricola and T. vitrinus. The reasons for differences observed in the prevalence of some helminthes among the two groups were discussed.